2021
DOI: 10.1007/s10336-021-01867-z
|View full text |Cite
|
Sign up to set email alerts
|

An iconic messenger of climate change? Predicting the range dynamics of the European Bee-eater (Merops apiaster)

Abstract: When environmental conditions change, species usually face three options: adaptation, range shifts, or extinction. In the wake of climate change, it is generally believed that range shifts are the norm in mobile species such as birds, resulting in poleward range shifts. The European Bee-eater is a predominantly Mediterranean species which has expanded its range to higher latitudes over the last decades. Germany in particular has seen a surge in breeding pairs and foundation of new colonies. However, while many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 79 publications
0
29
0
Order By: Relevance
“…However, 13 of the 31 farmland species showed significant positive trends, highlighting that species-specific drivers can occur and determine different demographic responses. For instance, some thermophilic farmland species, such as the European Bee-eater, showed strong positive trends, probably favored by temperature increasing [ 167 , 168 , 169 ]. Woodland birds, which appear stable or increasing in Europe [ 22 , 43 , 170 ], confirmed this pattern in our study area.…”
Section: Discussionmentioning
confidence: 99%
“…However, 13 of the 31 farmland species showed significant positive trends, highlighting that species-specific drivers can occur and determine different demographic responses. For instance, some thermophilic farmland species, such as the European Bee-eater, showed strong positive trends, probably favored by temperature increasing [ 167 , 168 , 169 ]. Woodland birds, which appear stable or increasing in Europe [ 22 , 43 , 170 ], confirmed this pattern in our study area.…”
Section: Discussionmentioning
confidence: 99%
“…Habitat suitability has been linked to population size and trends in birds (Green et al, 2008;Stiels et al, 2021). We showed that large areas of the study region are predicted as suitable in the future, and that a stable mean habitat suitability is likely.…”
Section: Discussionmentioning
confidence: 76%
“…However, the two RCPs employed in our study can provide valuable insights on the effect of global change on habitat suitability, as demonstrated by their extensive use (e.g. Kiss et al, 2020;Stiels et al, 2021). We also limited our study to the breeding period:…”
Section: S1mentioning
confidence: 99%
See 1 more Smart Citation
“…That is, low abundances (and hence lower genetic diversity) could reduce local rates of adaptation at range edges, with gene flow from the abundant range center swamping any effect of local adaptation at the range edge that would facilitate range expansion when conditions change (Haldane, 1956; but see Kottler et al, 2021). Studies on invasive species have the potential to improve our understanding of the mechanisms that promote expansion from original range boundaries (e.g., the tolerance niche of the Asian Openbill Bird - Lei & Liu, 2021; and climate matching in the European Bee-eater - Stiels et al, 2021).…”
Section: Are Species Particularly Rare At Their Range Limits?mentioning
confidence: 99%